A magyarországi és finnországi hosszú távú társadalmi fejlődés a társadalmi jelzőszámok idősorai alapján - Andorka, Rudolf (Szociológiai Szemle, 2024)
The paper investigates the nature of social development in Hungary since 1945, by comparing time series of Hungarian and Finnish social indices. Three alternative theories are considered: (1) Hungarian, socialist development has fundamentally differed from capitalist development in Finland, (2) social development was determined by industrialization in both countries, producing remarkable similarities, and (3) the socialist and the capitalist route of development represent two variants of the industrial society with significant differences. The author finds that a comparison of the indices of economic development, income distribution, social mobility, time budget, mortality, deviant behaviour, and life quality support the last among the above alternatives. Differences between the Finnish and the Hungarian social development are most conspicuous in mortality, deviance, and the quality of life.